Key components in the professional ethics of sign language interpreters in healthcare contexts: a qualitative study in Colombia - Nora Ellen Groce; Samia Hurst; Laura Catalina Izquierdo Martínez; Angela Martínez-R; Jessica Cuculick; Minerva C Rivas Velarde (BMJ Open)
Objectives To identified the core components of professional ethics for medical sign language interpreters and develop a framework based on empirical data from Colombian sign language (CSL) interpreters.Design Purposive and snowball sampling methods were used in this qualitative study, which involved conducting semistructured interviews to CSL interpreters. Inductive data analysis was performed using the constant comparative method, where data collection and analysis occurred simultaneously. Transcriptional coding was performed line by line, and the data results were organised into themes and subthemes.Setting The research was conducted in Colombia.Participants A total of 17 CSL interpreters were included.Results We identified key themes (confidentiality, privacy, professionalism, business practices and professional development). Our data analyses show the need for codes of conduct and establishment of professional codes of ethics for sign language interpreters working in a health context. The proposed framework addresses the challenges within the professional ethics of sign language interpreters in healthcare.Conclusions These findings offer unique insights into the ethical experiences of CSL interpreters. This framework can be a valuable reference for interpreters facing ethical dilemmas. The clarity of ethical considerations is crucial for overcoming barriers to healthcare for the D/deaf population. The identified ethical issues underscore the necessity of education, training and the establishment of codes of ethics and legislation for sign language interpreters. These findings can serve as a foundational reference for crafting ethical guidelines for sign language interpreters in other low- and middle-income countries.